2020
DOI: 10.1021/acsomega.0c02399
|View full text |Cite
|
Sign up to set email alerts
|

Pore Structure and Fractal Characteristic Analysis of Gasification-Coke Prepared at Different High-Temperature Residence Times

Abstract: An accurate and quantitative description of the pore structure of gasification-coke using fractal geometry could be of great significance to its industrial utilization. In this study, gasification-coke was prepared with low-quality coal blending at different high-temperature residence times to investigate the variation in the pore structure, fractal dimensions, reactivities, and their relationship. The pore structure parameters (e.g., specific surface area, pore volume, and average pore diameter) of gasificati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 59 publications
(113 reference statements)
0
6
0
Order By: Relevance
“…According to fractal theory, self-similar fractal behavior does not change with the scale of magnification. 10 , 22 , 41 Since its introduction by Mandelbrot in 1977, it has been widely used in pore structure evaluation and characterization. 42 , 43 The self-similarity behavior of pore structures can be illustrated by eq 1 .…”
Section: Sampling and Methodologymentioning
confidence: 99%
See 1 more Smart Citation
“…According to fractal theory, self-similar fractal behavior does not change with the scale of magnification. 10 , 22 , 41 Since its introduction by Mandelbrot in 1977, it has been widely used in pore structure evaluation and characterization. 42 , 43 The self-similarity behavior of pore structures can be illustrated by eq 1 .…”
Section: Sampling and Methodologymentioning
confidence: 99%
“…The traditional methods such as the Euclidean geometry and experimental techniques are no longer effective in characterizing and evaluating complex and heterogeneous pore structures . Numerous studies have demonstrated that pore structures in porous rocks are self-similar and do not change with investigation scales. ,, By applying the fractal theory, complex pore systems can be quantitatively investigated, and the fractal dimensions obtained can also be applied for reservoir quality evaluation and estimation of petrophysical properties . Fractal analysis has been shown to be especially suitable for characterizing low-permeability terrestrial sandstones that have undergone complex diagenetic modifications …”
Section: Introductionmentioning
confidence: 99%
“…19 After the reaction of coke with CO 2 , the change in big pores is much more complicated than that in small pores. 20 The minerals in coke, such as Ca and Fe, enhance the gasification. Specifically, Ca has a higher influence on the gasification of coke.…”
Section: Introductionmentioning
confidence: 99%
“…The changes in the coke structure and pore due to the gasification reaction lead to changes in the coke strength after gasification . After the reaction of coke with CO 2 , the change in big pores is much more complicated than that in small pores . The minerals in coke, such as Ca and Fe, enhance the gasification.…”
Section: Introductionmentioning
confidence: 99%
“…The present work is closely related to two streams of literature: coal pore structure characteristics and coal fractal characteristics. In the study of Guo et al (2020), low quality blended coal is used as raw material to prepare gasified-coke under different residence time, and the changes of pore structure and fractal dimension are investigated. Their findings indicate that the pore structure characteristics, such as specific surface area, pore volume, and average pore diameter, at different residence times are continuous and complete.…”
Section: Introductionmentioning
confidence: 99%